Arbuscular mycorrhizal fungal communities in soils where astragalus had grown for 2 years were similar to those in the abandoned farmland - An, Zhi-Gang; Shang, Hu-Shan; Cui, Zhi-Jia; Huang, Yu-Fang; Wu, Rui; Li, Run-Hong (Frontiers in Microbiology, 2024)
Purpose Astragalus-cultivated soils are enriched in arbuscular mycorrhizal fungi (AMF); however, the community changes of AMF between years in stragalus-cultivated soils are still unclear. Methods To illustrate this, using high-throughput amplicon sequencing and quantitative real-time PCR, we analyzed the AMF communities of the abandoned farmlands and interannual astragalus-cultivated soils for 1-, 2-, 3-, and 4-years, including community composition, dominant, core, specific and significantly fluctuating AMF, co-occurrence network, alpha diversity, and beta diversity. Results A total of 74 OTUs were classified into one phylum, Glomeromycota; one class, Glomeromycetes; four orders; four families; and six genera. The 2-year soil had the highest number of reads among the interannual soils. Only one OTU was shared among all interannual soils. The treatments significantly affected the Ace, Shannoneven, and Shannon estimators of the communities. The 2-year soil had the highest richness, evenness, and diversity among all interannual soils and was the closest to the abandoned farmland in terms of alpha diversity. Glomus of the family Glomeraceae was the dominant genus present in all treatments, and the composition of the dominant genus in interannual soils was different. Both Glomus and Diversispora were the core AMF in interannual soils, and specific AMF existed in different interannual soils. Glomus is a genus that exhibits significant interannual variation. The interannual time significantly affected the network connectivity. The results of the principal coordinate analysis showed that the community composition of the interannual soils was close to each other and separated from the abandoned farmland, and that the interannual time significantly affected the community composition. Conclusion Among the interannual soils, the 2-year soil may be more suitable for A. sinensis seedling rotation.